Counseling on Early Prevention of Stunting at Maccini Sombala - Evi Sri Dahrianti; Rasdin Rasdin; Muhammad Idhan; Nengsiana Nengsiana (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2024)
Stunting is a serious public health problem, especially in developing countries. The impact of stunting on children's growth and development can have long-term impacts on the health and productivity of individuals and society. Counseling on the early prevention of stunting is crucial to reducing the prevalence of stunting. The purpose of this activity is to increase knowledge about the importance of eating healthy and nutritionally balanced foods for elementary school children. The method used in this activity is counseling about the importance of knowledge about stunting and distributing leaflets. The results based on the evaluation have increased public knowledge about the importance of a healthy diet and good nutrition to prevent stunting and the development of educational programs on balanced nutrition and healthy food practices for pregnant women and toddlers. Conclusion stunting can be prevented early by communicating and working together between the village government and district government, and very important is the role of the Puskesmas. PkM activities can make a positive contribution to society, whether in terms of increasing knowledge, changing behavior, or improving overall well-being. Therefore, it is important to ensure that the results of PkM can be implemented and sustained over a long period of time